Isotrema guangdongense (Aristolochiaceae), a new species from Guangdong, South China - Xu, Lian-Sheng; Li, Tian; Xu, Ye-Chun; Chen, You-Sheng (Phytotaxa, 2023)
Isotrema guangdongense (Aristolochiaceae), a new species from Guangzhou, Guangdong Province, South China, is described and illustrated. This new species is similar to I. kwangsiense in its habit, cordate leaves, and yellow throat of calyx tube. However, it differs from the latter by its leaves puberulous or glabrous adaxially, abaxially densely villous (vs. both surfaces moderately to densely hirsute), flower usually solitary (vs. racemes 2–3 flowered), pedicel 4–7 cm long (vs. pedicel 2.5–3.5 cm long), calyx abaxially whitish with purple-red stripes and yellow to brown villous (vs. yellowish, abaxially densely rusty hirsute), limb adaxially white with dense big purple spinous processes while abaxially pale white (vs. adaxially dark purple with dense big purple spinous processes while abaxially pale yellowish green), and throat of calyx limb ca. 10–17 mm in diam. (vs. 5–6 mm in diam.).